2017
DOI: 10.1007/s40618-017-0758-z
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound variants of autoimmune thyroiditis in children and adolescents and their clinical implication in relation to papillary thyroid carcinoma development

Abstract: Background The prevalence of autoimmune thyroiditis (AIT) and papillary thyroid carcinoma (PTC) is rising in children and adolescents, and the coincidence of AIT and PTC is as high as 6.3–43%.ObjectiveTo investigate the ultrasound manifestation of AIT in relation to PTC development in paediatric patients.Patients179 paediatric patients (133 females), mean (SD) age: 13.9 (3.03) years diagnosed with AIT and referred for ultrasound evaluation. Eight patients were diagnosed with PTC (6 females). MethodsRetrospecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
29
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(33 citation statements)
references
References 28 publications
4
29
0
Order By: Relevance
“…However, such a relationship between AIT and papillary, medullary, and anaplastic TC was not shown [21]. It has been observed that there is a correlation between a higher concentration of TSH and the frequency of f PTC in patients with AIT and nodular goitre [22].…”
Section: Casementioning
confidence: 99%
“…However, such a relationship between AIT and papillary, medullary, and anaplastic TC was not shown [21]. It has been observed that there is a correlation between a higher concentration of TSH and the frequency of f PTC in patients with AIT and nodular goitre [22].…”
Section: Casementioning
confidence: 99%
“…The sonographic appearance of lymphocytic thyroiditis varies, likely reflecting the phase and severity of the disease process [12]. In our previous work, we presented five ultrasonographic variants of autoimmune thyroiditis in children (in decreasing frequency): (1) the most common form of diffuse thyroiditis with a hypoechogenic background and normoechogenic parenchyma, (2) diffuse thyroiditis with an irregular background, (3) a nodular variant with a normoechogenic irregular background, (4) micronodulations, and (5) a variant with a diffuse hypoechogenic background [18]. We also reported that patients with the nodular AIT variant with a normoechogenic irregular background of the thyroid gland are at risk of developing PTC and should be followed up with regular neck ultrasound (US) assessments [18].…”
Section: Introductionmentioning
confidence: 99%
“…In the general paediatric population, the incidence of thyroid nodules is 1–18% [19]. In AIT patients, the incidence of thyroid nodules is 13–30% [1820]. The co-existence of AIT and PTC ranges between 6.3 and 43% depending on the patient population and continues to rise [18, 19, 2125].…”
Section: Introductionmentioning
confidence: 99%
“…All the six studies included in the final analysis were retrospective. The 11 studies included a total number of 2,065 patients with HT, with individual study cohorts counting from 89 to 904 children [20][21][22][23][24][25].…”
Section: Resultsmentioning
confidence: 99%
“…The following results were observed in 179 patients: hypoechogenic background and normoechogenic parenchyma (35.2%), thyroiditis with irregular background (30.2%), nodular variant with normoechogenic background (18.9%), micronodulations (11.7%) and diffuse hypoechogenic background (3.9%). Janus et al concluded that patients with AIT and nodular variant with normoechogenic irregular background of the thyroid gland on US scans are in the risk group of developing PTC and should be followed up with regular ultrasound investigations [23].…”
Section: Resultsmentioning
confidence: 99%